Diagnosis of Autism using an Eye Tracking System - Vargas-Cuentas, Natalia I. (2016)
Autism Spectrum Disorders (ASD) are characterized by a deficit in social integration, language development, and restricted interests. ASD is defined as a prevalence development life disability. However, children who are early diagnosed and intervention improve long-term prognosis. This project proposes to detect autism in children at a first level (preclinical stage) using a tool "eye tracking" highly cost-effective and embedded in a tablet. The results obtained with this system have been compared with the outcomes of the Modified Autism in Children M-CHAT questionnaire.